Agricultural water use and trade in Uzbekistan: situation and potential impacts of market liberalization - Abdullaev, Iskandar; Fraiture, Charlotte de; Giordano, Mark; Yakubov, Murat; Rasulov, A. (Informa UK Limited, 2009)
The focus in Uzbekistan on cotton and its irrigation led to large increases in water use with significant downstream impacts, particularly on the Aral Sea. While agriculture is still heavily influenced by the state, Uzbekistan has become more integrated in the global economy since its independence. The major goal of this paper is to examine the interrelationship between agricultural policies and water use during the last 15 years and how moves towards freer markets, such as those which might occur under the World Trade Organization, may impact Uzbekistan's water resources in the future. The results show that partial or full market liberalization may result in an increase in water use. However, the greater message is that non-water policies can have a major impact on water outcomes and therefore should be considered in any discussions of water sector reform.